Pengaruh Pemberian Ekstrak Nanas Terhadap Kualitas Tahu Susu - Rita Purwasih; Enceng Sobari; Sri Puri Andani (LPPM Perjuangan University of Tasikmalaya, 2021)
This research aims to determine the effect of differences in the administration of pineapple extract on the quality of milk tofu. The benefit of this research is that it can determine the effect of different pineapple extracts on the quality of milk tofu. The experimental design used was Completely Randomized Design (CRD) with 3 treatments and 3 replications, with T0 treatment adding 35 ml vinegar acid, T1 adding Queen pineapple extract 70ml, T2 adding Cayenne pineapple extract 70 ml. The parameters observed were protein content, and hedonic tests namely color, taste, aroma, and texture. The data generated were analyzed with Analysis of Variance (ANOVA) with a significance level of 5%. The hedonic test data were analyzed using Kruskal Wallis. If there is a real effect, followed by Duncan's test. The results obtained are that there are differences in the administration of pineapple extract on the taste and texture of tofu milk. Tofu milk with the addition of 70 ml Queen pineapple extract (T1) is the best treatment. Keywords: bromelin, hedonic, quality, pineapple, protein, tofu.